Engineering the Mechanics and Thermodynamics of Ti3AlC2, Hf3AlC2, Hf3GaC2, (ZrHf)3AlC2, and (ZrHf)4AlN3 MAX Phases via the Ab Initio Method - Adel Bandar Alruqi (Crystals)
When combined with ceramics, ternary carbides, nitrides, and borides form a class of materials known as MAX phases. These materials exhibit a multilayer hexagonal structure and are very strong, damage tolerant, and thermally stable. Further, they have a low thermal expansion and exhibit outstanding resistance to corrosion and oxidation. However, despite the numerous MAX phases that have been identified, the search for better MAX phases is ongoing, including the recently discovered Zr3InC2 and Hf3InC2. The properties of MAX phases are still being tailored in order to lower their ductility. This study investigated Ti3AlC2 alloyed with nitrogen, gallium, hafnium, and zirconium with the aim of achieving better mechanical and thermal performances. Density functional theory within Quantum Espresso module was used in the computations. The Perdew–Burke–Ernzerhof generalised gradient approximation functionals were utilised. (ZrHf)4AlN3 exhibited an enhanced bulk and Young’s moduli, entropy, specific heat, and melting temperature. The best thermal conductivity was observed in the case of (ZrHf)3AlC2. Further, Ti3AlC2 exhibited the highest shear modulus, Debye temperature, and electrical conductivity. These samples can thus form part of the group of MAX phases that are used in areas wherein the above properties are crucial. These include structural components in aerospace and automotive engineering applications, turbine blades, and heat exchanges. However, the samples need to be synthesised and their properties require verification.